Criteria for Classification of Inter-Radicular Septum Shape in Maxillary Molars with Clinical Importance for Immediate Implant Placemen - Khalid, Sana; Sharif, Mubashir; Rehman, Anis ur; Abbas, Asifa; Ayub, Wagma; Azad, Naseem (Pakistan Armed Forces Medical Journal, 2025)
Objective: To explore the use of Cone Beam Computed Tomography to evaluate morphometric properties of the Inter-Radicular Septum in maxillary first and second molar region.Study Design: Cross-sectional study.Place and Duration of Study: Armed Forces Institute of Dentistry, Combined Military Hospital, Rawalpindi Pakistan, from Jul to Dec 2023.Methodology: Cone Beam Computed Tomography scans of 177 patients, recruited via consecutive sampling technique were obtained and analyzed using NEWTOM software. Patients falling in the age range of 18-65 years, having first and second maxillary molars were included. The Inter-Radicular Septum morphometric properties of maxillary first and second molars were evaluated in coronal and axial plane. Inter-Radicular Septum widths and areas of M1 and M2 were compared at different levels by applying ANOVA/Kruskal Wallis test based upon data normalityResults: Out of 177 patients, 118(66.7%) were males, while 59(33.3%) were females with mean age 40.49±1.33 years. Frequency of arrow shape of molars (M1&M2) was highest [119(67.2%) and 136(76.8%) respectively]. Mean difference of Inter-Radicular Septum widths across all levels was significantly varied with respect to shapes of Molar 1 and Molar 2 as well (p